Ta’lim al-Lughah al-Arabiyyah ‘ala Asasi e-Mobile Instrumental - Zubaidi, Ahmad (UIN Syekh Wasil Kediri, Indonesia, 2019)
This study aims to develop a model of Arabic learning based on e-mobile instrumental using the appypie application. The method used in this study is a qualitative type, in which the authors use Contex Analysis as data analysis from primary sources in the form of appypie applications and Arabic learning material in jer letters. After the writer conducted the research, the design of the Arabic learning model based on e-mobile instrumental showed that the researcher tried to create a quality e-mobile that had been designed so that it also had an impact with the creation of quality learning. In addition, the design of e-mobile in Arabic learning based on e-mobile instrumental developed in this study only refers to one topic or one Arabic material as an example, namely the “Jer Letters”. E-mobile is presented using the appypie application. Then found the advantages of this learning model are saving time, giving more space in learning, greater motivation in learning Arabic, more encouraging students because of e-mobile based, and saving material. The disadvantages of this Arabic learning model are difficulties for students who do not have internet data packages, need time to check the quality of the existing internet, cannot control students directly, lack of learning evaluation features, and the application is still paid